Emigration, return and re-emigration in the first half of the twentieth century - Tiago de Oliveira, Isabel (2007)
This research compares legal emigration and net migration in Portugal between 1890 and 1970. The difference between these migration indicators shows the relative significance of movements unaccounted for in the official statistics: return, re-emigration, illegal emigration, and movements to and from the colonies. This analysis suggests that return and re-emigration were more significant up to 1940, and that since that time illegal emigration and departures to the colonies have taken over.